Different Cytoplasmic Calcium Contents Among Three Species of Characeae - Tazawa, Masashi; Kikuyama, Munehiro; Okazaki, Yoshiji (Plant and Cell Physiology, 2001)
Internodal cells of three species of Characeae, Nitella flexilis , Nitella axilliformis and Chara corallina , were analyzed for the contents of Ca2+ and Mg2+ in the cytoplasm. To avoid contamination of Ca2+ from the cell wall and vacuole, the vacuolar sap was replaced with a sorbitol solution containing Sr2+ by the vacuolar perfusion method after the cell had been treated with Sr2+. No significant difference in the cytoplasmic content of Mg2+ was found among three species of Characeae, but significant differences in the cytoplasmic content of Ca2+ were observed among them. The cytoplasmic Ca2+ content of N. flexilis was 2.0 times that of N. axilliformis and 3.3 times that of C. corallina . The cytoplasmic drop was furthermore separated into two fractions: a chloroplast-free fraction and a chloroplast fraction. In the chloroplast-free fraction the Ca2+ content of N. flexilis was 2.3 times that of C. corallina and 2.0 times that of N. axilliformis , while the Mg2+ content was the same among the three species. In the chloroplast fraction N. flexilis contained about seven times more Ca2+ and about two times more Mg2+ than C. corallina . The difference in the cytoplasmic Ca2+ content was discussed in relation to the difference in the capacity for the hydration-induced Ca2+ release existing among the three species.